Jahresbericht 1993 - Kunstgesellschaft Luzern. - Kunstmuseum Luzern, Luzern (Luzern : Kunstgesellschaft Luzern, 1994)
E Boetti, Alighiero ; Mullican, Matt ; Wall, Jeff ; Streuli, Beat ; Filliou, Robert ; Fischer, Alexander ; Hodel, Ernst ; Kunz, Rainer ; Kunz, Peter ; Mosbacher, Alois ; Hecht, David ; Erenberg, Sam ; etc.
Duits
boek